Education and Training as a Means of Developing MSME Expertise - Sutrisno, Sutrisno; Permana, Riko Mersandro; Junaidi, Ahmad (ADMAN: Journal of Contemporary Administration and Management, 2023)
The important role of MSMEs in the economy cannot be ignored, as they create jobs and contribute to economic growth significantly. However, in the midst of increasingly fierce competition in the era of globalisation and information technology, MSMEs face various challenges to maintain and develop their businesses. This study aims to examine the role of education and training as a means of developing the skills of MSMEs. This research is a literature review using a qualitative approach, which implies that data will be analysed and interpreted with reference to information and texts obtained from various sources. The results of this study show that education and training play a very important role in developing the skills and competitiveness of Micro, Small and Medium Enterprises (MSMEs). MSMEs play a strategic role in a country's economy, but they often face constraints such as limited knowledge, skills, capital and market access. Education and training provide key benefits in improving the competencies, skills, and knowledge needed by MSMEs to run their businesses more efficiently, optimise operations, and make smarter decisions. In addition, education and training also help MSMEs to innovate, adapt to market and technological changes, and understand regulatory aspects of business.